Unveiling the hurdles confronting compressed biogas plants: a comprehensive research analysis for sustainable energy solution - Ghag, Nikhil; Shedage, Sujit; Sonar, Harshad; Jagtap, Sandeep (Springer, 2025)
The purpose of this work is to identify and analyze the key important barriers to uptake the compressed biogas (CBG) plants in India for enhancing their role as a sustainable energy source. Initially, the barriers are identified from the past academic literature using literature review process and are then validated through the fuzzy Delphi method with expert opinions. The finalized barriers were then categorized into cause effect relationship and ranked for strategic decision making by policy makers, investors, and industry practitioners. We employed the weighted influence non-linear gauge systems (WINGS) method to find hierarchical relationships and determine the priority of these barriers. The findings provide a strategic roadmap for policymakers, investors, and industry stakeholders to enhance CBG adoption through supply chain improvements, financial incentives, public awareness campaigns, and regulatory streamlining. By systematically identifying, linking, and ranking interrelated barriers, the study develops a structured and data-driven framework that provides actionable strategies for accelerating the adoption of compressed biogas (CBG) plants in India.
Keywords: 46 Information and Computing Sciences; 4609 Information Systems; 35 Commerce, Management, Tourism and Services; 7 Affordable and Clean Energy; Supply chain management; Compressed biogas; Sustainability; Energy management